2008
DOI: 10.1016/j.jbiomech.2007.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Validation of CFD predictions of flow in a 3D alveolated bend with experimental data

Abstract: Verifying numerical predictions with experimental data is an important aspect of any modeling studies. In the case of the lung, the absence of direct in-vivo flow measurements makes such verification almost impossible. We performed computational fluid dynamics (CFD) simulations in a 3D scaled-up model of an alveolated bend with rigid walls that incorporated essential geometrical characteristics of human alveolar structures and compared numerical predictions with experimental flow measurements made in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Few of such studies have shown validation of their CFD methodology (Allen et al, 2004;Croce et al, 2006;van Ertbruggen et al, 2008). However, due to limitation that arises due to inaccessibility, inaccuracy, and invasiveness of clinical measurements, it is challenging to validate computational results.…”
Section: Discussionmentioning
confidence: 99%
“…Few of such studies have shown validation of their CFD methodology (Allen et al, 2004;Croce et al, 2006;van Ertbruggen et al, 2008). However, due to limitation that arises due to inaccessibility, inaccuracy, and invasiveness of clinical measurements, it is challenging to validate computational results.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the complex flow patterns in the pulmonary region with increasingly more sophisticated geometries: a rigid axisymmetric circular model (Tsuda et al, 1995), a torus on a tube (Tippe and Tsuda, 2000), an expanding threedimensional (3D) single alveoli (Haber et al, 2003), square channels (Karl et al, 2004), square channels on a bend (van Ertbruggen et al, 2008), 3D terminal alveolar sac with spherical alveoli (Oakes et al, 2010), 3D terminal alveolar sac with 14-hedron alveoli (Sznitman et al, 2007b(Sznitman et al, , 2009, and terminal sac with octahedron shaped alveoli (Kumar et al, 2009). It is clear from these studies that flow in the pulmonary region involves recirculation to varying degrees depending on geometry, flow rate, and cyclic wall motion.…”
Section: Introductionmentioning
confidence: 99%
“…Following this approach, a CFD model was obtained that replicated the in vitro irrigation model with a great degree of similarity and incorporated all of its geometry and physical parameters. In CFD studies, the use of an unsuitable turbulence model may lead to potential numerical errors in CFD results [ 218 ]. In a study by Gao et al [ 108 ], four turbulent models [low Reynolds k-ε, low Reynolds renormalization group k-ε, transitional fl ow k-ω, and transitional fl ow shear stress transport (SST) k-ω] were used to simulate root canal irrigation because these turbulent models are suitable for studying fl ow with low Re.…”
Section: Mathematical Virtual Simulation Modelsmentioning
confidence: 99%